Echinococcus granulosus genotype G1 dominated in cattle and sheep during 2003–2006 in Buenos Aires province, an endemic area for cystic echinococcosis in Argentina - Andresiuk, Maria Vanesa (2013)
Cystic echinococcosis (hydatidosis) is a severe and widespread disease, caused by the larval stage of the tapeworm Echinococcus granulosus; it affects large numbers of humans and farm animals annually, causing serious health and economic problems. Molecular studies have identified large genetic variation within the E. granulosus complex, with various hosts displaying different susceptibility to different genotypes. For the effective management of the disease, one of the most pressing tasks is to combine epidemiological and genetic data to better understand the role of different hosts and genotypes in the transmission of the parasite. The aim of the present study was to describe the epidemiology of cystic echinococcosis in cattle and sheep, and to characterise the genotypes of E. granulosus present in these farm animals. The study was carried out in the Pampa region of Argentina, with a particular focus on Buenos Aires province, where cystic echinococcosis represents an important human and veterinary health problem. Among 513 cattle and 792 sheep, 11.9% and 4.0%, respectively, were infected with E. granulosus. Genetic characterisation of 42 isolates from cattle and 34 isolates from sheep was carried out by sequencing mitochondrial cox1 and nad1 genes. The vast majority of isolates were identified as genotype G1, except for a single sheep isolate determined as genotype G2, and a single cattle isolate that corresponded to genotype G5. Genotype G1 has previously been found to be the most infectious genotype to humans. As G1 was also the genotype principally responsible for cystic echinococcosis in Buenos Aires province, these results have important implications for developing effective disease control programmes to improve human and animal healthcare in this region.